Ein Arbeitsmarktprogramm für Europa - Holger Schäfer; Jörg Schmidt; Henning Klodt; Gerhard Bosch; Hilmar Schneider (Wirtschaftsdienst, 2012)
Die Europäische Kommission hat ein Beschäftigungspaket vorgestellt, das die Erwerbstätigkeit in der EU verbessern und erhöhen soll, aber auch einen Ausweg aus der Krise darstellen könnte. Eine Umsetzung erscheint unrealistisch vor allem, weil die Arbeitsmärkte in der EU stark differieren, die EU über keine angemessenen Instrumente verfügt und das Programm bisher nicht in einen Wachstumspakt eingebunden ist. Die Autoren halten es zudem für konzeptionslos. – – The European Employment Strategy is the subject of controversial discussion. It is hard to fi nd an economic justifi cation for transnational responsibility since European labour markets are heterogenous and spillover effects of national employment policies are almost negligible. In its latest communication, the European Commission fails to provide a masterplan for a recovery of the struggling labour markets, although it provides convincing and less convincing proposals for tackling unemployment in EU member states. There is a suspicion that the package mainly serves as a fi rst step towards transferring employment policy responsibilities from the national to the EU level. But the EU labour market policy lacks appropriate instruments and competences. Finally, it is questionable whether the package fi ts in an economic growth plan.
Keywords: E61; J08; 330; Erwerbstätigkeit; Beschäftigungspolitik; EU-Politik; Beschäftigungseffekt; EU-Staaten